Implementing Green Transformational Leadership to improve the Green HR Practices and Green Employee Behavior to provide Sustainable Organizational Performance - Sari, Lia Wijaya; Soelton, Mochamad (Journal of Sustainable Economic and Business, 2024)
Implementing green energy policies into human resource practices can encourage the creation of a positive environment. Sustainable development strategies for environmental sustainability are developing rapidly in various companies in facing challenges and natural disasters caused by ecosystem damage, environmental pollution, climate change and energy instability. This research aims to analyze the influence of Green Human Resources Practices and Green Employee Behavior on Sustainable Organizational Performance with the mediation of Green Transformational Leadership. The research population is employees who have a minimum position of supervisor, the sample is 78 food and beverage division supervisors. Quantitative research using probability sampling techniques. The survey used a questionnaire method and a Structural Equation Model (SEM) approach with the Smart-PLS analysis tool. Research findings, Employee Green Behavior, Green Human Resource Practices, have a significant positive effect on Green Transformational Leadership. Employee Green Behavior, Green Human Resource Practices, have a significant positive effect on Sustainable Organization Performance. Environmentally friendly transformational leadership has a significant positive effect on sustainable organizational performance. Environmentally friendly transformational leadership does not mediate the influence of environmentally friendly employee behavior on sustainable organizational performance, environmentally friendly transformational mediates the influence of environmentally friendly leadership human resource practices.